Optimalisasi Media Sosial Sebagai Promosi Public Relations Pantai Parai Tenggiri - Trisagia Mokodongan; Anggun Mawar Pertiwi (Jurnal Penelitian Ilmu Pariwisata, 2025)
Social media is currently the primary channel for disseminating tourism information. Optimal media use is not only a promotional tool but also a form of PR communication in building a destination's image. This study analyzes the use of social media as a promotional tool for public relations (PR) at Parai Tenggiri Beach, Bangka Islands. The method used is a descriptive qualitative approach through observation and interviews at Parai Tenggiri Beach to determine the optimization of social media. The results show that the use of social media is still not optimal due to the lack of digital communication strategies, two-way interactions between managers and tourists, and the minimal use of persuasive communication techniques. The gap between the visual potential and the public relations promotion used needs to be evaluated to strengthen the role of PR in creating creative and sustainable digital communication.